Proceedings of the 9th Annual Conference on Genetic and Evolutionary Computation 2007
DOI: 10.1145/1276958.1277203
|View full text |Cite
|
Sign up to set email alerts
|

A study on metamodeling techniques, ensembles, and multi-surrogates in evolutionary computation

Abstract: Surrogate-Assisted Memetic Algorithm(SAMA) is a hybrid evolutionary algorithm, particularly a memetic algorithm that employs surrogate models in the optimization search. Since most of the objective function evaluations in SAMA are approximated, the search performance of SAMA is likely to be affected by the characteristics of the models used. In this paper, we study the search performance of using different metamodeling techniques, ensembles, and multisurrogates in SAMA. In particular, we consider the SAMA-TRF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…To reduce the needed number of expensive function evaluations, surrogate-assisted evolutionary algorithms (SAEAs) [22], [8], [21] can be used, where the main idea is to use one [23], [24] or multiple surrogates [25], [26], [27] to approximate the expensive function evaluation globally or locally [28], [29], [30]. Note that an implicit assumption here is that the computational cost for constructing and using the surrogates is much less than that for fitness evaluations using the original expensive function.…”
Section: B Surrogate Models and Surrogate Managementmentioning
confidence: 99%
“…To reduce the needed number of expensive function evaluations, surrogate-assisted evolutionary algorithms (SAEAs) [22], [8], [21] can be used, where the main idea is to use one [23], [24] or multiple surrogates [25], [26], [27] to approximate the expensive function evaluation globally or locally [28], [29], [30]. Note that an implicit assumption here is that the computational cost for constructing and using the surrogates is much less than that for fitness evaluations using the original expensive function.…”
Section: B Surrogate Models and Surrogate Managementmentioning
confidence: 99%
“…rmse of the 20 clustered localized models for variable levels of residual error tolerances, while taking the original airfoil analysis code as the reference model (i.e., with a fidelity of 1) case, this implies the correlation between the predicted fitness values is of utmost importance. For greater details, the reader is referred to [16][17][18], where it was shown that the correlation metric represents a more useful metric for estimating the quality of an approximation model over one that is based on absolute error.…”
Section: Multi-fidelity Models In the Aerodynamic Airfoil Design Problemmentioning
confidence: 99%
“…Particularly, local models are used in favor of global models since constructing accurate global models is fundamentally flawed due to the curse of dimensionality [18][19][20][21]. Further, this allows more precise estimation on the unique characteristics of the problem landscapes, thus leading to the prediction on the appropriate level of localized model fidelity over the use of the original computationally expensive model.…”
Section: : End Whilementioning
confidence: 99%
“…Currently, the common fitness estimation methods include the fitness inheritance and the application of surrogate model [11][12][13][14][15][16][17]. However, which method will perform better in fitness estimation?…”
Section: Introductionmentioning
confidence: 99%